Analysis of Teacher Professional Development at SDN Caturtunggal 4 Yogyakarta - Niendy; Fakhriya Nusaima; Yuliana Aisya; Muhammad Syukron; Wiji Hidayati (IAIN Parepare, 2025)
This study aims to analyze the implementation of the teacher professional development program at SDN Caturtunggal 4 Yogyakarta in order to improve the competence and quality of learning. The research used descriptive qualitative methods with data collection techniques through in-depth interviews, direct observation, and documentation studies. The results show that professional development is carried out through various forms of training, such as Teacher Working Group (KKG) activities, webinars, Teacher Professional Education Program (PPG), and internal school training called